Pengaruh Pembelajaran dengan Metode Pemberian Tugas dan Resitasi terhadap Hasil Belajar Biologi Siswa Kelas XI SMA Negeri 3 Makassar - Firdaus, Daud (bionature, 2010)
This  was  a  quasy experiment involving control group and experiment  one  in which the subject was the students of class XI of  SMA Negeri 3 Makassar in the school year of 2008/2009. The aim of the research were  to  knowledge  the  effect  of  the  learning  method  in  which  the  students  were  given  assignments  and recitation and to compare the study results of the students who were given the assignment and recitation with those who were not. It was done by using  Posttest-Only Control Design.  The number of the subject was 81 which  was  chosen  by  cluster  random  sampling  from  365  students.  It  was  then  divided  into  two  groups: experiment group (41 subjects) and control group (40 subjects). The study results of the students in Biology Subject were analyzed by using descriptive statistic and inferensial one. It was shown that  the mean of the study results of the students who were given assignment and recitation was higher than of those who were not (t  2,846 > 0,716  with α = 0,05).  In conclusion, taking assignment and recitation in the learning process has a positive influence significantly to the study results of the students.